2020
DOI: 10.1515/biol-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Vip3Aa1 against Periplaneta americana

Abstract: AbstractBacillus thuringiensis (Bt) is a well-known entomopathogen. In this study, we cloned the vip3Aa1 gene from Bt strain GIM1.147 and investigated the insecticidal activity of Bt Vip3Aa1 protein produced by Escherichia coli against Periplaneta americana and Blattella germanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Initially, it was shown that Vip3 was lepidopteran specific. However, activity against other insect targets, such as the cockroach species Periplaneta americana and Blattella germanica ( 60 ), and the mosquito species Aedes aegypti ( 61 ), has been reported. Unlike Cry toxins, which accumulate in parasporal bodies inside the bacterial sporangium, Vip3 proteins are secreted by the Bt bacterium during the vegetative growth phase, and their production continues during the sporulation growth phase ( 62 ).…”
Section: Structural Changes Of Vip3 Toxins During Pore Formationmentioning
confidence: 99%
“…Initially, it was shown that Vip3 was lepidopteran specific. However, activity against other insect targets, such as the cockroach species Periplaneta americana and Blattella germanica ( 60 ), and the mosquito species Aedes aegypti ( 61 ), has been reported. Unlike Cry toxins, which accumulate in parasporal bodies inside the bacterial sporangium, Vip3 proteins are secreted by the Bt bacterium during the vegetative growth phase, and their production continues during the sporulation growth phase ( 62 ).…”
Section: Structural Changes Of Vip3 Toxins During Pore Formationmentioning
confidence: 99%
“…Therefore, it is necessary to interpret more comprehensive and subtle morphological features in order to supplement and improve the morphological descriptions. There have been many reports on the hematoxylin -Eosin (HE) staining and paraffin sections of insects [10][11][12][13][14], however, there are fewer reports about the tissue structure of biting midges. In this paper, the morphology and ultrastructure of both adult sexes of C. grisescens were observed and described in detail by SEM, describing its characteristic morphology.…”
Section: Introductionmentioning
confidence: 99%